Evaluation of oil recovery by alkali/surfactant flooding in multi-layered carbonate reservoirs with different pore sizes - Arnon Larpkachornsanguan (Chulalongkorn University, 2014)
Thesis (M.Eng.)--Chulalongkorn University, 2012